2023
DOI: 10.1111/mmi.15069
|View full text |Cite
|
Sign up to set email alerts
|

Study of NIT domain‐containing chemoreceptors from two global phytopathogens and identification of NIT domains in eukaryotes

Abstract: Bacterial signal transduction systems are typically activated by the binding of signal molecules to receptor ligand binding domains (LBDs), such as the NIT LBD. We report here the identification of the NIT domain in more than 15,000 receptors that were present in 30 bacterial phyla, but also in 19 eukaryotic phyla, expanding its known phylogenetic distribution. The NIT domain formed part of seven receptor families that either control transcription, mediate chemotaxis or regulate second messenger levels. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Typhimurium (14,32). SCRI1043 has a single chemosensory pathway (14), and the chemoreceptors analyzed thus far respond to amino acids (PacB, PacC), quaternary amines (PacA), and nitrate (PacN) (37)(38)(39). We show here that there are very significant differences in the affinity of the individual pentapeptides for CheR that are reflected in differences in the magnitude of the chemotactic responses.…”
Section: Introductionmentioning
confidence: 79%
“…Typhimurium (14,32). SCRI1043 has a single chemosensory pathway (14), and the chemoreceptors analyzed thus far respond to amino acids (PacB, PacC), quaternary amines (PacA), and nitrate (PacN) (37)(38)(39). We show here that there are very significant differences in the affinity of the individual pentapeptides for CheR that are reflected in differences in the magnitude of the chemotactic responses.…”
Section: Introductionmentioning
confidence: 79%
“…This lack of knowledge is partly due to the fact that the major model species in chemotaxis research have alternative lifestyles. Research has so far shown that phytopathogen chemoreceptors respond to a number of compounds of the general metabolism like amino acids (Cerna‐Vargas et al., 2019 ; Kumar Verma et al., 2018 ; McKellar et al., 2015 ; Tumewu et al., 2021 ; Velando et al., 2023 ), organic acids (Hida et al., 2015 , 2019 ), quaternary amines (Matilla, Velando, Tajuelo, et al., 2022 ) or nitrate (Gálvez‐Roldán et al., 2023 ; Monteagudo‐Cascales et al., 2023 ). Although these molecules are not plant‐specific compounds, they are present at high concentrations in plant exudates (Lohaus, 2022 ); Vives‐Peris et al., 2020 ) and are therefore major signals for host recognition.…”
Section: What Do We Know About Phytopathogen Chemoreceptor Function?mentioning
confidence: 99%
“…Although this method identifies ligands that bind to LBDs, it fails to monitor chemoreceptor activation by non‐canonical mechanisms or stimulation by ligand‐loaded solute binding proteins. However, the combined use of in vivo and in vitro approaches is a powerful set‐up to identify the function of chemoreceptors in plant pathogens, as illustrated by a number of examples (Cerna‐Vargas et al., 2019 ; Gálvez‐Roldán et al., 2023 ; Monteagudo‐Cascales et al., 2023 ; Santamaría‐Hernando et al., 2022 ; Velando et al., 2023 ).…”
Section: Experimental Approaches Aimed At Closing the Gap In Phytopat...mentioning
confidence: 99%
“…Phage ΦM1 encodes a DNA genome approximately 44 kb long, organized into 52 putative genes. The host bacterium for ΦM1, P. atrosepticum, is a globalGram-negative potato pathogen found in both temperate and tropical regions, and is known to colonize the intercellular spaces of plant cells and degrade the cell wall, causing blackleg disease and aerial stem rot (22,23). Recent studies have focused on identifying biocontrol agents against P. atrosepticum, including antimicrobial chemicals, zinc/silver nanoparticles, and antagonistic bacterial isolates (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%